2021
DOI: 10.2147/amep.s314644
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Personality Traits and Learning Styles on Undergraduate Medical Students’ Academic Achievement

Abstract: Purpose: Learning focus has shifted from conventional teacher-centered to student-centered; therefore, methods used to support and encourage learners must be considered. Meanwhile, the individual differences between learners should be taken into consideration by medical educators. Aiming to achieve a better learning experience, the current study investigates the relationship between personality traits and learning styles and their effect on students' academic achievement. Subjects and Methods: An analytical, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 29 publications
1
33
0
2
Order By: Relevance
“…It has been well recognized that GPA, which relies on an average of scores, is a more accurate assessment of achievement. 3 While the utility of senior medical students has been briefly acknowledged by Abouzeid et al, 1 we also suggest using GPA as a measure of academic success. This would enable the authors to further fulfill their aim of improving the learning experience at medical school, by diversifying the applicability of results and exploring how students alter their learning style as they gain more clinical exposure in the later years.…”
Section: Dear Editormentioning
confidence: 80%
See 1 more Smart Citation
“…It has been well recognized that GPA, which relies on an average of scores, is a more accurate assessment of achievement. 3 While the utility of senior medical students has been briefly acknowledged by Abouzeid et al, 1 we also suggest using GPA as a measure of academic success. This would enable the authors to further fulfill their aim of improving the learning experience at medical school, by diversifying the applicability of results and exploring how students alter their learning style as they gain more clinical exposure in the later years.…”
Section: Dear Editormentioning
confidence: 80%
“…We read with great interest the article by Abouzeid et al, 1 discussing the influence of personality traits and learning styles on academic achievement. As sixth year medical students, we have undertaken teaching modules ourselves, and recognize the importance of tailoring revision to learning styles in order to maximize academic success.…”
Section: Dear Editormentioning
confidence: 99%
“…In a study performed by Duarte, Lopes, and da Silva (2021) the performance of the mechanical engineering students at the University of Porto was correlated with their performance at the end of high school, but found no significant correlation between these two factors. Moreover, learning style and its components are defined as a key factor that influences the learning process of the students and their academic performance (Abouzeid et al 2021), and these factors are based on the individual differences (Biabani and Izadpanah 2019). Various models e.g., Virtual Aural Read/Write Kinesthetic (VARK) model (Abouzeid et al 2021), Dunn & Dunn Model (Schick 1979), andGrasha model (McLaughlin 1996) are used to categorize the learning styles which relate to the way one learns and differs from individual to individual (Phoong, Phoong, and Phoong 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, learning style and its components are defined as a key factor that influences the learning process of the students and their academic performance (Abouzeid et al 2021), and these factors are based on the individual differences (Biabani and Izadpanah 2019). Various models e.g., Virtual Aural Read/Write Kinesthetic (VARK) model (Abouzeid et al 2021), Dunn & Dunn Model (Schick 1979), andGrasha model (McLaughlin 1996) are used to categorize the learning styles which relate to the way one learns and differs from individual to individual (Phoong, Phoong, and Phoong 2021). Kolb and Kolb (2006) defined four fundamental learning styles e.g., activist, reflector, theorist and pragmatist.…”
Section: Introductionmentioning
confidence: 99%
“…Another study involving medical students from the United Kingdom which assessed the relationship between the big five personality traits, perfectionism, and psychological distress concluded that low levels of conscientiousness and emotional stability were associated with poor mental health [14]. Moreover, the most common personality traits found in medical undergraduates from Egypt were agreeableness and openness [15]. Another field of study related various personality dimensions to the preference of a certain specialty among the medical students.…”
Section: Introductionmentioning
confidence: 99%